2016
DOI: 10.1002/star.201500304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrocolloids on acorn starch physical properties

Abstract: The effect of hydrocolloids (arabic gum, carrageenan, carboxymethyl cellulose, and xanthan gum) on the physical properties of acorn starch was investigated. First order mixture response surface model was used and the effects of 1% hydrocolloids on acorn starch water holding capacity, starch solution viscosity, gel strength, freeze-thaw stability, and pasting properties were evaluated. Contributions of each hydrocolloid on determining acorn starch functionality were also calculated. Hydrocolloid combinations si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…Compared to WF, DAF contained less protein (3.81%), and ash (0.40%); but more fat (1.07%) and starch (77.97%). This is consistent with the results in the previous literature suggesting that acorn flour contains more than 55% of starch, 2.75-8.44% protein, and 0.7-7.4% fat [21].…”
Section: Physicochemical Properties Of Floursupporting
confidence: 93%
“…Compared to WF, DAF contained less protein (3.81%), and ash (0.40%); but more fat (1.07%) and starch (77.97%). This is consistent with the results in the previous literature suggesting that acorn flour contains more than 55% of starch, 2.75-8.44% protein, and 0.7-7.4% fat [21].…”
Section: Physicochemical Properties Of Floursupporting
confidence: 93%
“…Galactomannans (guar and locust bean gum) increased the transition temperatures (To, Tp, and Tc) and decreased the gelatinization enthalpy (DH) [51]. e use of different hydrocolloids (Arabic gum, carrageenan, carboxymethyl cellulose, and xanthan gum) to improve the functionality of acorn starch has also been reported [52]. According to this study, the addition of hydrocolloids significantly increased the flow behavior indices, consistency coefficient, gel strength, and pasting properties.…”
Section: Modifications and Uses Of Starchmentioning
confidence: 53%
“…Acron flow behavior index and consistency coefficient varied with the egg and wheat starch contribution in each treatment. Previous study on the effect of hydrocolloids on the physical properties of acorn starch by Saleh, Ajo, Al‐Ismail, and Ondier () suggested that acorn starch viscoelastic behavior is influenced by the variation in treatments chemical composition and water availability. The authors further indicated that the magnitude of change in flow behavior index and consistency coefficient for acorn starch is a function of acorn starch–hydrocolloids interaction.…”
Section: Resultsmentioning
confidence: 99%